(untitled) (Bangladesh Critical Care Journal, 2017)
Combined pulmonary fibrosis and emphysema (CPFE) is rare but increasingly recognized condition characterized by simultaneous coexistence of both upper lobe predominant emphysema and diffuse pulmonary fibrosis mainly in lower lobe. Patients with CPFE are usually heavy smokers or former smokers. HRCT has a pivotal role in diagnosis. Pulmonary function test showed relatively preserved lung volumes and reduced diffusing capacity of the lung for carbon monoxide (DLCO). Development of pulmonary hypertension (PH) is largely attributed to morbidity in patients with CPFE which is the principal prognostic factor for this condition. However more studies are needed to establish natural history of the disease & treatment option. In this review, we will discuss the current knowledge of the pathogenesis, clinical characteristics, treatment options and prognostic factors of CPFE. Bangladesh Crit Care J September 2017; 5(2): 122-125